Helicobacter Pylori-Associated Idiopathic Thrombocytopenic Purpura: A Narrative Review - Franchini, Massimo; Vescovi, Pier Paolo; Garofano, Massimo; Veneri, Dino (Seminars in Thrombosis and Hemostasis, 2012)
The Gram-negative bacterium Helicobacter pylori has a well-demonstrated role in several gastroduodenal diseases, including peptic ulcer disease, chronic active gastritis, mucosa-associated lymphoid tissue lymphoma, and gastric adenocarcinoma. In addition, more recently, several studies have focused on the possible causal role of H. pylori in various extragastric disorders, such as cardiovascular, respiratory, neurological, skin, and autoimmune conditions. The current status of the research on the pathogenesis, clinical and therapeutic aspects of H. pylori-associated idiopathic thrombocytopenic purpura in adults and children will be addressed in this narrative review.
Keywords: Helicobacter pylori; thrombocytopenia; bleeding; eradication therapy